A Case Report on the Effect of Triphala Decoction in Tartar-Induced Periodontitis in Dentistry (AYUSHDHARA, 2023)
Dental tartar causes irritation and inflammation in gingival tissue. Further, it attacks the soft periodontal tissue which supports the teeth. Therefore, all supragingival and subgingival tartar was removed by an ultrasonic scaler on the 1st day, and the patient was advised to swish Triphala (equal amount of Amla, Haritaki, and Vibhitaki) decoction in the oral cavity from the evening on the same day of scaling. The lukewarm decoction was kept in the oral cavity for 10 minutes and then swallowed. It was given twice a day for 30 days after the meal. The patient was advised to visit on the 7th, 15th, and 30th day of follow-up. Triphala itself has an antimicrobial property. Its decoction kept in the oral cavity stimulated the saliva flow. Saliva has lysozymes that have a bactericidal effect on the oral micro-organisms. Triphala expelled the toxins from the gut by increasing the peristalsis movement of GIT. It had a digestive stimulant property which increased the digestive fire and improved overall oral health. As the Triphala decoction showed very effective results on scaling wound, it may be used as herbal mouthwash in the future. Besides, Triphala powder is easily available, economical, and has negligible side effects.